A method for preparing low shrinkage concrete

By modifying coconut fiber and basalt powder, functional composites are formed, which solves the problems of dispersion and corrosion resistance of existing low-shrink concrete, and achieves high-strength and long-term stable concrete preparation.

CN118754573BActive Publication Date: 2025-01-17WEIFANG CONSTR ENG CONCRETE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411252020.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-17
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Existing low-shrink concretes have defects in fiber dispersion and corrosion resistance, resulting in low strength and short service life.

Method used

By modifying coconut fiber and basalt powder, their dispersion and compatibility are improved, functional composite materials are formed, and homogenized with cement and other components, a low shrinkage, high strength and corrosion resistance are prepared. Concrete.

Benefits of technology

The low shrinkage and high strength properties of concrete are achieved, ensuring the stability and long-term service life of the structure, significantly improving the tensile strength, flexural strength and split tensile strength, and showing good durability in corrosion environments .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a preparation method of low shrinkage concrete, belonging to the technical field of concrete; the compounding step comprises: placing modified coconut fiber in acetone, stirring evenly, adding modified basalt powder, stirring at 180-220 rpm for 23-27 minutes, adding dibutyltin dilaurate after the stirring is completed, raising the temperature to 63-67 DEG C, stirring and reacting for 9.8-10.2 hours, filtering and washing after the reaction is completed, placing at -25-21 DEG C for precooling and drying for 4.3-4.7 hours, placing at -42-38 DEG C for freeze drying for 7.8-8.2 hours, and naturally recovering to room temperature to obtain a functionalized composite material; the concrete prepared by the method of the invention has good low shrinkage, high strength and excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and particularly relates to a method for preparing low-shrinkage concrete. Background Art

[0002] Low shrinkage concrete is a type of concrete with lower shrinkage properties. It can effectively reduce the volume shrinkage of concrete during the setting and hardening process, reduce the occurrence of cracks, has good volume stability, and ensures the durability and safety of concrete structures. It is widely used in bridge engineering, super high-rise buildings and other fields.

[0003] The shrinkage cracking of concrete is closely related to the amount of water inside. Fibers have good water absorption and moisture retention properties. Adding them to concrete can continuously provide moisture to the interior of the concrete, which can effectively slow down the self-drying and self-shrinkage problems inside the concrete, thereby enhancing the volume stability of the concrete and reducing cracking performance.

[0004] To this end, the prior art discloses the following method:

[0005] CN115611582A discloses a low shrinkage, fast-setting, early-strength concrete and a preparation method thereof, wherein the raw materials include water, cement, slag, medium sand, crushed stone, water reducing agent, reinforcing filler, mixed fiber, polyvinyl alcohol, and organic acid; wherein the mixed fiber includes two or more of coconut fiber, chitin fiber, and polypropylene short fiber; the method has the effect of reducing the drying shrinkage of the early-strength concrete and improving the crack resistance of the early-strength concrete;

[0006] However, the method for preparing concrete in this patent is to add composite fibers directly into concrete, which will cause problems such as difficulty in dispersion and poor adhesion to the matrix, thereby reducing the flexural strength of the concrete and making the strength performance unstable. The strength performance of the corroded concrete is greatly reduced, seriously shortening its service life.

[0007] CN114434595A discloses a low shrinkage high-strength concrete and a preparation method thereof, specifically disclosing that cement, fly ash, quartz sand, nano boron nitride powder, desulfurized gypsum powder, diamond-type titanium dioxide, zeolite powder, sodium metasilicate, magnesium stearate, and light magnesium oxide are subjected to primary mixing, nitridation treatment, polymer surface modification, vacuum cold treatment, and post-treatment to reduce shrinkage and enhance strength properties such as compressive strength and flexural strength;

[0008] However, the concrete prepared by this patent has the defect of poor corrosion resistance.

[0009] It can be seen that the low shrinkage concrete obtained by adding water-absorbent fibers in the prior art has the following defects:

[0010] 1. The fiber has poor dispersion and poor adhesion to the matrix, resulting in low strength of the concrete;

[0011] 2. Concrete has poor corrosion resistance. Summary of the invention

[0012] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing low shrinkage concrete, which has low shrinkage, high strength performance and excellent corrosion resistance.

[0013] In view of the above technical problems, the present invention adopts the following technical solutions:

[0014] A method for preparing low shrinkage concrete comprises the following steps:

[0015] 1. Preparation of modified coconut fiber

[0016] (1) Primary

[0017] The coconut fiber is placed in a nitric acid solution, the temperature is increased to 70-74°C, and the mixture is stirred at 70-74°C for 35-43 minutes at a stirring speed of 348-372 rpm. After the stirring is completed, the mixture is filtered and dried to obtain oxidized coconut fiber. The oxidized coconut fiber is placed in an ethanol solution, sodium fatty acid methyl ester sulfonate and nonylphenol polyoxyethylene ether are added, the temperature is increased to 58-63°C, and the mixture is stirred. After the mixture is stirred evenly, primary coconut fiber is obtained.

[0018] The coconut fiber has a diameter of 130-150 nm and a length of 0.2-0.4 mm;

[0019] The mass concentration of the nitric acid solution is 60-64%;

[0020] The mass ratio of the coconut fiber to the nitric acid solution is 9.5-10.6:70-82;

[0021] The mass ratio of the oxidized coconut fiber, the ethanol solution, the sodium fatty acid methyl ester sulfonate and the nonylphenol polyoxyethylene ether is 9.0-9.7:60-68:0.4-0.6:0.5-0.8;

[0022] The mass concentration of the ethanol solution is 50-55%;

[0023] (2) Modification

[0024] The diphenylmethane diisocyanate is placed in acetone, stirred evenly, and then primary coconut fiber is added for ultrasonic treatment. The ultrasonic time is 12-15 minutes, the ultrasonic power is 92-97W, and the ultrasonic frequency is 38-43kHz. After the ultrasonic treatment, the temperature is raised to 62-65°C at a rate of 0.6-0.8°C / min, and the reaction is carried out at 62-65°C for 3.0-3.5 hours. After the reaction is completed, the modified coconut fiber is obtained by filtering, washing, and drying.

[0025] The mass volume ratio of the diphenylmethane diisocyanate, acetone and primary coconut fiber is 2.2-2.4 g:310-330 mL:1.42-1.46 g.

[0026] 2. Preparation of Modified Basalt Powder

[0027] The basalt powder is placed in a sealed container, and an ethanol solution is introduced. After stirring, sodium α-olefin sulfonate and octadecyl dimethyl betaine are added, and the mixture is stirred again. Then, the treatment liquid is added dropwise at a rate of 0.8-1.2 g / min. The mixture is stirred while adding, and the stirring speed is 290-308 rpm. After the addition is completed, the temperature is raised to 71-74°C at a rate of 1.8-2.2°C / min, and the pressure is controlled to be 1.3-1.5 MPa. The mixture is kept warm for 4.8-5.2 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain ammoniated basalt powder. The aminated basalt powder is placed in xylene, and maleic anhydride is added after stirring. The temperature is raised to 123-127°C for stirring reaction. The reaction time is 13-15 hours, and the stirring speed is 175-185 rpm. After the reaction is completed, the mixture is filtered, washed, and dried to obtain modified basalt powder.

[0028] The particle size of the basalt powder is 105-115nm;

[0029] The mass concentration of the ethanol solution is 37-42%;

[0030] The mass ratio of the basalt powder, ethanol solution, sodium α-olefin sulfonate, octadecyl dimethyl betaine and treatment liquid is 8.2-8.6:64-70:0.2-0.4:0.4-0.6:12.0-12.5;

[0031] The treatment liquid is a mixture of 35wt% ethanol solution, diethylenetriaminepropyltrimethoxysilane and triethanolamine, wherein the mass ratio of the 35wt% ethanol solution, diethylenetriaminepropyltrimethoxysilane and triethanolamine is 10-12:0.7-0.9:0.3-0.5;

[0032] The mass volume ratio of the ammoniated basalt powder, xylene and maleic anhydride is 5.0-5.4 g:220-235 mL:1.7-1.9 g.

[0033] 3. Compound

[0034] The modified coconut fiber is placed in acetone, stirred evenly, and then the modified basalt powder is added, and stirred at 180-220 rpm for 23-27 minutes. After the stirring is completed, dibutyltin dilaurate is added, and the temperature is increased to 63-67°C, and the reaction is stirred for 9.8-10.2 hours. After the reaction is completed, it is filtered and washed, and pre-cooled and dried at -25 to -21°C for 4.3 to 4.7 hours, and then freeze-dried at -42 to -38°C for 7.8 to 8.2 hours, and naturally restored to room temperature to obtain a functional composite material;

[0035] The mass volume ratio of the modified coconut fiber, acetone, modified basalt powder and dibutyltin dilaurate is 2.0-2.2g:195-205mL:4.8-5.2g:0.22-0.24g.

[0036] 4. Mixing

[0037] The cement, mineral powder and fly ash are mixed and stirred evenly, and then crushed stone, river sand and vermiculite are added, and after stirring evenly again, functional composite materials, polycarboxylate water reducer, sodium lignin sulfonate, fatty alcohol polyoxyethylene ether and deionized water are added, and homogenization treatment is performed. The homogenization time is 2.5-3.5min, the homogenization pressure is 2.8-3.1MPa, and the homogenization number is 3 times. After the homogenization treatment is completed, low shrinkage concrete is obtained;

[0038] The cement is P·O42.5 silicate cement;

[0039] The particle size of the fly ash is 38-42 μm;

[0040] The particle size of the crushed stone is 6.4-6.6 mm;

[0041] The particle size of the river sand is 1.3-1.7 mm;

[0042] The vermiculite has a particle size of 5.4-5.6 mm and a density of 2.57-2.62 g / cm 3 , the mass content of silicon dioxide is 40.3-41.2%;

[0043] The mass ratio of the cement, mineral powder, fly ash, crushed stone, river sand, vermiculite, functional composite material, polycarboxylic acid water reducer, sodium lignin sulfonate, fatty alcohol polyoxyethylene ether and deionized water is 10.3-10.7:3.8-4.2:3.7-3.9:34-38:23-25:15-17:6.1-6.3:0.2-0.4:0.10-0.14:0.12-0.15:15.7-16.3.

[0044] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0045] 1. The present invention first performs an oxidation treatment on the coconut fiber, and then disperses it in sodium fatty acid methyl ester sulfonate and nonylphenol polyoxyethylene ether, thereby improving the surface activation performance of the coconut fiber and increasing the hydroxyl active group. After the modification step of diisocyanate, the primary coconut fiber reacts with diisocyanate to obtain isocyanate-modified coconut fiber; the basalt powder is modified to increase the dispersibility of the basalt powder, and amino groups are grafted on the surface, and then the ring-opening amidation reaction is carried out with maleic anhydride to enhance the affinity of the basalt powder with other components. Compatibility: The modified basalt powder is compounded with the modified coconut fiber, and the amino groups react with the isocyanate groups. The obtained functional composite material presents a relatively stable network structure. The basalt powder and coconut fiber have strong bonding and stable connection, which ensures the water absorption and wetting properties of the functional composite material. It can continuously and effectively provide moisture to the interior of the concrete, ensure the low shrinkage performance of the concrete, and enhance the strength performance. The concrete obtained by combining it with other technical means has a uniform structure, stable properties, high and stable strength performance, and greatly extends the service life;

[0046] 2. The concrete prepared by the method of the present invention has a tensile strength of 87.7-89.5 MPa, a flexural strength of 19.7-21.5 MPa, and a splitting tensile strength of 7.9-8.2 MPa according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete";

[0047] 3. The concrete prepared by the method of the present invention has a 28d shrinkage rate of 0.00025-0.00029% according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete";

[0048] 4. The concrete prepared by the method of the present invention was placed in a 30wt% hydrochloric acid solution and allowed to stand for 5 days, washed 3 times and dried, then placed in a 30wt% sodium chloride solution and allowed to stand for 5 days, washed 3 times and dried, and the tensile strength was measured again to be 82.9-85.6MPa, the flexural strength was 18.8-20.7MPa, and the splitting tensile strength was 7.4-7.8MPa. DETAILED DESCRIPTION

[0049] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.

[0050] Example 1

[0051] 1. Preparation of modified coconut fiber

[0052] (1) Primary

[0053] 10 g of coconut fiber was placed in 75 g of nitric acid solution, the temperature was raised to 72° C., and the mixture was stirred at 72° C. for 40 min at a stirring speed of 360 rpm. After the stirring was completed, the mixture was filtered and dried to obtain oxidized coconut fiber. 9.4 g of oxidized coconut fiber was placed in 64 g of ethanol solution, 0.5 g of sodium fatty acid methyl ester sulfonate and 0.6 g of nonylphenol polyoxyethylene ether were added, the temperature was raised to 60° C., and the mixture was stirred. After the mixture was stirred evenly, primary coconut fiber was obtained.

[0054] The coconut fiber has a diameter of 140 nm and a length of 0.3 mm;

[0055] The mass concentration of the nitric acid solution is 62%;

[0056] The mass concentration of the ethanol solution is 52%;

[0057] (2) Modification

[0058] 2.3 g of diphenylmethane diisocyanate was placed in 320 mL of acetone, stirred evenly, and then 1.44 g of primary coconut fiber was added for ultrasonic treatment. The ultrasonic time was 14 min, the ultrasonic power was 95 W, and the ultrasonic frequency was 41 kHz. After the ultrasonic treatment, the temperature was raised to 64 ° C at a rate of 0.7 ° C / min, and the reaction was carried out at 64 ° C for 3.2 h. After the reaction was completed, the modified coconut fiber was obtained by filtering, washing, and drying.

[0059] 2. Preparation of Modified Basalt Powder

[0060] 8.4 g of basalt powder was placed in a sealed container, 67 g of ethanol solution was introduced, and after stirring, 0.3 g of sodium α-olefin sulfonate and 0.5 g of octadecyl dimethyl betaine were added, and the mixture was stirred again. Then, 12.2 g of the treatment solution was added dropwise at a rate of 1.0 g / min, and the mixture was stirred while adding. The stirring speed was 300 rpm. After the addition was completed, the temperature was raised to 73°C at a rate of 2.0°C / min, and the pressure was controlled to be 1.4 MPa. The mixture was kept warm for 5.0 h. After the end of the warm reaction, the mixture was filtered, washed, and dried to obtain ammoniated basalt powder. 5.2 g of ammoniated basalt powder was placed in 230 mL of xylene, and after stirring, 1.8 g of maleic anhydride was added. The temperature was raised to 125°C for stirring reaction. The reaction time was 14 h, and the stirring speed was 180 rpm. After the end of the stirring reaction, the mixture was filtered, washed, and dried to obtain modified basalt powder.

[0061] The particle size of the basalt powder is 110 nm;

[0062] The mass concentration of the ethanol solution is 40%;

[0063] The treatment liquid is a mixture of 35 wt % ethanol solution, diethylenetriaminopropyltrimethoxysilane and triethanolamine, and the mass ratio of the 35 wt % ethanol solution, diethylenetriaminopropyltrimethoxysilane and triethanolamine is 11:0.8:0.4.

[0064] 3. Compound

[0065] Place 2.1 g of modified coconut fiber in 200 mL of acetone, stir evenly, then add 5.0 g of modified basalt powder, stir at 200 rpm for 25 min, add 0.23 g of dibutyltin dilaurate, raise the temperature to 65 ° C, stir and react for 10 h, filter and wash after the reaction, pre-cool and dry at -23 ° C for 4.5 h, then freeze-dry at -40 ° C for 8.0 h, and naturally return to room temperature to obtain a functional composite material.

[0066] 4. Mixing

[0067] 10.5g cement, 4.0g mineral powder, 3.8g fly ash were mixed and stirred evenly, then 36g crushed stone, 24g river sand and 17g vermiculite were added, and after stirring evenly again, 6.2g functional composite material, 0.3g polycarboxylate water reducer, 0.10g sodium lignin sulfonate, 0.13g fatty alcohol polyoxyethylene ether and 16.0g deionized water were added, and homogenization treatment was performed. The homogenization time was 3.0min, the homogenization pressure was 3.0MPa, and the homogenization number was 3 times. After the homogenization treatment was completed, low shrinkage concrete was obtained;

[0068] The cement is P·O42.5 silicate cement;

[0069] The particle size of the fly ash is 40 μm;

[0070] The particle size of the crushed stone is 6.5 mm;

[0071] The particle size of the river sand is 1.5 mm;

[0072] The vermiculite has a particle size of 5.5 mm and a density of 2.6 g / cm 3 , the mass content of silicon dioxide is 40.8%.

[0073] Example 2

[0074] 1. Preparation of modified coconut fiber

[0075] (1) Primary

[0076] 9.5 g of coconut fiber was placed in 70 g of nitric acid solution, the temperature was raised to 70° C., and the mixture was stirred at 70° C. for 35 min at a stirring speed of 348 rpm. After the stirring was completed, the mixture was filtered and dried to obtain oxidized coconut fiber. 9.0 g of oxidized coconut fiber was placed in 60 g of ethanol solution, 0.4 g of sodium fatty acid methyl ester sulfonate and 0.5 g of nonylphenol polyoxyethylene ether were added, the temperature was raised to 58° C., and the mixture was stirred. After the mixture was stirred evenly, primary coconut fiber was obtained.

[0077] The diameter of the coconut fiber is 130nm and the length is 0.2mm;

[0078] The mass concentration of the nitric acid solution is 60%;

[0079] The mass concentration of the ethanol solution is 50%;

[0080] (2) Modification

[0081] 2.2 g of diphenylmethane diisocyanate was placed in 310 mL of acetone, stirred evenly, and then 1.42 g of primary coconut fiber was added for ultrasonic treatment. The ultrasonic time was 12 min, the ultrasonic power was 92 W, and the ultrasonic frequency was 38 kHz. After the ultrasonic treatment, the temperature was raised to 62 ° C at a rate of 0.6 ° C / min, and the reaction was carried out at 62 ° C for 3.0 h. After the reaction was completed, the modified coconut fiber was obtained by filtering, washing, and drying.

[0082] 2. Preparation of Modified Basalt Powder

[0083] 8.2g of basalt powder was placed in a sealed container, 64g of ethanol solution was introduced, and after stirring, 0.2g of sodium α-olefin sulfonate and 0.4g of octadecyl dimethyl betaine were added, and the mixture was stirred again. Then, 12.0g of the treatment solution was added dropwise at a dropping rate of 0.8g / min. The mixture was stirred while dropping at a stirring speed of 290rpm. After the addition was completed, the temperature was raised to 71°C at a rate of 1.8°C / min, the pressure was controlled to be 1.3MPa, and the mixture was kept warm for 4.8h. After the end of the warm reaction, the mixture was filtered, washed, and dried to obtain ammoniated basalt powder. 5.0g of ammoniated basalt powder was placed in 220mL of xylene, and after stirring, 1.7g of maleic anhydride was added, the temperature was raised to 123°C for stirring reaction, the reaction time was 13h, and the stirring speed was 175rpm. After the end of the stirring reaction, the mixture was filtered, washed, and dried to obtain modified basalt powder.

[0084] The particle size of the basalt powder is 105 nm;

[0085] The mass concentration of the ethanol solution is 37%;

[0086] The treatment liquid is a mixture of 35 wt % ethanol solution, diethylenetriaminopropyltrimethoxysilane and triethanolamine, and the mass ratio of the 35 wt % ethanol solution, diethylenetriaminopropyltrimethoxysilane and triethanolamine is 10:0.7:0.3.

[0087] 3. Compound

[0088] Place 2.0 g of modified coconut fiber in 195 mL of acetone, stir evenly, then add 4.8 g of modified basalt powder, stir at 180 rpm for 23 min, add 0.22 g of dibutyltin dilaurate, raise the temperature to 63 ° C, stir and react for 9.8 h, filter and wash after the reaction, pre-cool and dry at -25 ° C for 4.3 h, then freeze-dry at -38 ° C for 8.2 h, and naturally return to room temperature to obtain a functional composite material.

[0089] 4. Mixing

[0090] 10.3g cement, 3.8g mineral powder, 3.7g fly ash were mixed and stirred evenly, then 34g crushed stone, 23g river sand and 15g vermiculite were added, and after stirring evenly again, 6.1g functional composite material, 0.2g polycarboxylate water reducer, 0.12g sodium lignin sulfonate, 0.12g fatty alcohol polyoxyethylene ether and 15.7g deionized water were added, and homogenization treatment was performed. The homogenization time was 2.5min, the homogenization pressure was 3.1MPa, and the homogenization number was 3 times. After the homogenization treatment was completed, low shrinkage concrete was obtained;

[0091] The cement is P·O42.5 silicate cement;

[0092] The particle size of the fly ash is 38 μm;

[0093] The particle size of the crushed stone is 6.4 mm;

[0094] The particle size of the river sand is 1.3 mm;

[0095] The vermiculite has a particle size of 5.4 mm and a density of 2.57 g / cm 3 , the mass content of silicon dioxide is 40.3%.

[0096] Example 3

[0097] 1. Preparation of modified coconut fiber

[0098] (1) Primary

[0099] 10.6 g of coconut fiber was placed in 82 g of nitric acid solution, the temperature was raised to 74° C., and the mixture was stirred at 74° C. for 43 min at a stirring speed of 372 rpm. After the stirring was completed, the mixture was filtered and dried to obtain oxidized coconut fiber. 9.7 g of oxidized coconut fiber was placed in 68 g of ethanol solution, 0.6 g of sodium fatty acid methyl ester sulfonate and 0.8 g of nonylphenol polyoxyethylene ether were added, the temperature was raised to 63° C., and the mixture was stirred. After the mixture was stirred evenly, primary coconut fiber was obtained.

[0100] The diameter of the coconut fiber is 150nm and the length is 0.4mm;

[0101] The mass concentration of the nitric acid solution is 64%;

[0102] The mass concentration of the ethanol solution is 55%;

[0103] (2) Modification

[0104] 2.4 g of diphenylmethane diisocyanate was placed in 330 mL of acetone, stirred evenly, and then 1.46 g of primary coconut fiber was added for ultrasonic treatment. The ultrasonic time was 15 min, the ultrasonic power was 97 W, and the ultrasonic frequency was 43 kHz. After the ultrasonic treatment, the temperature was raised to 65 ° C at a rate of 0.8 ° C / min, and the reaction was carried out at 65 ° C for 3.5 h. After the reaction was completed, the modified coconut fiber was obtained by filtering, washing, and drying.

[0105] 2. Preparation of Modified Basalt Powder

[0106] 8.6g of basalt powder was placed in a sealed container, 70g of ethanol solution was introduced, and after stirring, 0.4g of sodium α-olefin sulfonate and 0.6g of octadecyl dimethyl betaine were added, and the mixture was stirred again. Then, 12.5g of the treatment solution was added dropwise at a rate of 1.2g / min, and the mixture was stirred while dropping. The stirring speed was 308rpm. After the addition was completed, the temperature was raised to 74°C at a rate of 2.2°C / min, and the pressure was controlled to be 1.5MPa. The mixture was kept warm for 5.2h. After the end of the warm reaction, the mixture was filtered, washed, and dried to obtain ammoniated basalt powder. 5.4g of ammoniated basalt powder was placed in 235mL of xylene, and after stirring, 1.9g of maleic anhydride was added. The temperature was raised to 127°C for stirring reaction. The reaction time was 15h and the stirring speed was 185rpm. After the end of the stirring reaction, the mixture was filtered, washed, and dried to obtain modified basalt powder.

[0107] The particle size of the basalt powder is 115 nm;

[0108] The mass concentration of the ethanol solution is 42%;

[0109] The treatment liquid is a mixture of 35 wt % ethanol solution, diethylenetriaminopropyltrimethoxysilane and triethanolamine, and the mass ratio of the 35 wt % ethanol solution, diethylenetriaminopropyltrimethoxysilane and triethanolamine is 12:0.9:0.5.

[0110] 3. Compound

[0111] Place 2.2 g of modified coconut fiber in 205 mL of acetone, stir evenly, then add 5.2 g of modified basalt powder, stir at 220 rpm for 27 min, add 0.24 g of dibutyltin dilaurate, raise the temperature to 67 ° C, stir and react for 10.2 h, filter and wash after the reaction, pre-cool and dry at -21 ° C for 4.7 h, then freeze-dry at -42 ° C for 7.8 h, and naturally return to room temperature to obtain a functional composite material.

[0112] 4. Mixing

[0113] 10.7g cement, 4.2g mineral powder, 3.9g fly ash were mixed and stirred evenly, then 38g crushed stone, 25g river sand and 17g vermiculite were added, and after stirring evenly again, 6.3g functional composite material, 0.4g polycarboxylate water reducer, 0.14g sodium lignin sulfonate, 0.15g fatty alcohol polyoxyethylene ether and 16.3g deionized water were added, and homogenization treatment was performed. The homogenization time was 3.5min, the homogenization pressure was 2.8MPa, and the homogenization number was 3 times. After the homogenization treatment was completed, low shrinkage concrete was obtained;

[0114] The cement is P·O42.5 silicate cement;

[0115] The particle size of the fly ash is 42 μm;

[0116] The particle size of the crushed stone is 6.6 mm;

[0117] The particle size of the river sand is 1.7 mm;

[0118] The vermiculite has a particle size of 5.6 mm and a density of 2.62 g / cm 3 , the mass content of silicon dioxide is 41.2%.

[0119] Comparative Example 1

[0120] Based on Example 1, the changes are as follows:

[0121] (1) In the primary treatment step, the step of "placing 9.4 g of oxidized coconut fiber in 64 g of ethanol solution, adding 0.5 g of sodium fatty acid methyl ester sulfonate and 0.6 g of nonylphenol polyoxyethylene ether, heating to 60° C. and stirring, stirring evenly to obtain primary coconut fiber" is omitted; in the modification step, an equal amount of primary coconut fiber is replaced by oxidized coconut fiber;

[0122] (2) In the step of preparing modified basalt powder, the step of "placing 5.2 g of ammoniated basalt powder in 230 mL of xylene, stirring evenly, adding 1.8 g of maleic anhydride, heating to 125°C for stirring reaction, the reaction time is 14 h, the stirring speed is 180 rpm, and after the stirring reaction is completed, filtering, washing and drying to obtain modified basalt powder" is omitted;

[0123] In the compounding step, the modified basalt powder was replaced by an equal amount of ammoniated basalt powder;

[0124] The rest of the operations are the same.

[0125] Comparative Example 2

[0126] Based on Example 1, the changes are as follows:

[0127] (1) In the step of preparing the modified coconut fiber, the modification step is omitted; in the compounding step, the modified coconut fiber is replaced by the primary coconut fiber in equal amount;

[0128] (2) In the step of preparing modified basalt, equal amounts of sodium α-olefin sulfonate and octadecyl dimethyl betaine are replaced with an ethanol solution, wherein the mass concentration of the ethanol solution is 40%;

[0129] The rest of the operations are the same.

[0130] Performance Testing

[0131] 1. The products prepared in Examples 1-3 and Comparative Examples 1-2 were used to make standard specimens according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The specimens were demolded 24 hours after molding, taken out after standard curing for 28 days, and naturally air-dried for 2 hours to prepare test specimens, and the compressive strength, flexural strength and splitting tensile strength of the test specimens were tested;

[0132] Standard specimens were made according to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The specimens were demoulded 24 hours after molding, taken out after standard curing for 28 days, and naturally air-dried for 2 hours to obtain test specimens, and the shrinkage rate of the test specimens was tested;

[0133] The results are as follows:

[0134]

[0135] 2. The products prepared in Example 1-3 and Comparative Example 1-2 were used to make standard specimens according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The specimens were demolded 24 hours after molding, taken out after standard curing for 28 days, and naturally air-dried for 2 hours to prepare test specimens. The test specimens were placed in a 30wt% hydrochloric acid solution and allowed to stand for 5 days. After being taken out, they were washed 3 times and dried, and then placed in a 30wt% sodium chloride solution and allowed to stand for 5 days. After being taken out, they were washed 3 times and dried, and the strength performance was tested again. The results are as follows:

[0136]

[0137] The present invention first performs oxidation treatment on coconut fiber, and then places it in sodium fatty acid methyl ester sulfonate and nonylphenol polyoxyethylene ether for dispersion, thereby improving the surface activation performance of coconut fiber and increasing hydroxyl active groups. After the diisocyanate modification step, the primary coconut fiber reacts with the diisocyanate to obtain isocyanate-modified coconut fiber; the basalt powder is modified to increase the dispersibility of the basalt powder, and amino groups are grafted on the surface. Then, the basalt powder is subjected to a ring-opening amidation reaction with maleic anhydride to enhance the compatibility of the basalt powder with other components. The modified basalt powder is composited with the modified coconut fiber, wherein the amino groups react with the isocyanate groups, and the obtained functional composite material presents a relatively stable network structure, and the basalt powder and the coconut fiber have strong bonding force and stable connection, thereby ensuring the water absorption and wetting performance of the functional composite material, being able to continuously and effectively provide moisture to the inside of the concrete, ensuring the low shrinkage performance of the concrete, and enhancing the strength performance. The concrete obtained by combining the basalt powder with other technical means has a uniform structure, stable properties, high and stable strength performance, and greatly extends the service life.

[0138] In Comparative Example 1, the coconut fiber is only oxidized and then modified with isocyanate. During the modification process, the coagulation force of the coconut fiber is relatively strong, and the modification effect of the isocyanate is insufficient. In addition, the reaction step of the ammoniated basalt powder and the maleic anhydride is omitted in Comparative Example 1. The coagulated coconut fiber is compounded with the ammoniated basalt powder, and the internal components of the prepared concrete are not uniform, which affects the low shrinkage performance and strength performance of the concrete, and the strength decreases significantly after corrosion.

[0139] In the step of modifying basalt in Comparative Example 2, sodium α-olefin sulfonate and octadecyl dimethyl betaine are replaced with ethanol solution, the mixing of basalt and the treatment liquid is uneven, and the amination is incomplete, which affects the reaction with maleic anhydride. In addition, Comparative Example 2 also omits the modification step of coconut fiber, resulting in weak bonding between coconut fiber and basalt powder and unstable connection, which leads to large shrinkage and reduced strength of concrete. The strength performance of the corroded concrete is greatly reduced, which seriously affects the service life of the concrete.

[0140] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.

[0141] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing low shrinkage concrete, characterized in that: The preparation method comprises the steps of preparing modified coconut fiber, preparing modified basalt powder, compounding and slurry mixing; The modified coconut fiber comprises primary processing and modification steps; The primary treatment step comprises placing the oxidized coconut fiber in an ethanol solution, adding sodium fatty acid methyl ester sulfonate and nonylphenol polyoxyethylene ether, heating to 58-63° C. and stirring, and after stirring evenly, obtaining primary coconut fiber; The modification step comprises placing diphenylmethane diisocyanate in acetone, stirring evenly, adding primary coconut fiber, and performing ultrasonic treatment. After the ultrasonic treatment, the temperature is raised to 62-65° C. at a rate of 0.6-0.8° C. / min, reacting at 62-65° C. for 3.0-3.5 hours, and filtering, washing, and drying after the reaction is completed to obtain modified coconut fiber. The steps of preparing the modified basalt powder are as follows: placing the basalt powder in a sealed container, introducing an ethanol solution, stirring evenly, adding sodium α-olefin sulfonate and octadecyl dimethyl betaine, stirring evenly again, and then dripping the treatment liquid at a dripping rate of 0.8-1.2 g / min, stirring while dripping, and a stirring speed of 290-308 rpm. After the dripping is completed, heating to 71-74° C. at a rate of 1.8-2.2° C. / min, controlling the pressure to 1.3-1.5 MPa, and heat-keeping reaction for 4.8-5.2 hours. After the heat-keeping reaction is completed, filtering, washing, and drying to obtain the aminated basalt powder; placing the aminated basalt powder in xylene, stirring evenly, adding maleic anhydride, heating to 123-127° C. for stirring reaction, the reaction time is 13-15 hours, and the stirring speed is 175-185 rpm. After the stirring reaction is completed, filtering, washing, and drying to obtain the modified basalt powder. The treatment liquid is a mixture of 35wt% ethanol solution, diethylenetriaminepropyltrimethoxysilane and triethanolamine; The compounding step comprises placing the modified coconut fiber in acetone, stirring evenly, adding the modified basalt powder, stirring at 180-220 rpm for 23-27 minutes, adding dibutyltin dilaurate after the stirring is completed, raising the temperature to 63-67° C., stirring and reacting for 9.8-10.2 hours, filtering and washing after the reaction is completed, precooling and drying at -25 to -21° C. for 4.3 to 4.7 hours, and then freeze-drying at -42 to -38° C. for 7.8 to 8.2 hours, and naturally recovering to room temperature to obtain the functionalized composite material.

2. The method for preparing low shrinkage concrete according to claim 1, characterized in that: In the primary step, the mass ratio of the oxidized coconut fiber, the ethanol solution, the sodium fatty acid methyl ester sulfonate and the nonylphenol polyoxyethylene ether is 9.0-9.7:60-68:0.4-0.6:0.5-0.8; The mass concentration of the ethanol solution is 50-55%.

3. The method for preparing low shrinkage concrete according to claim 1, characterized in that: In the primary treatment step, the coconut fiber is placed in a nitric acid solution, the temperature is raised to 70-74° C., and the solution is stirred at 70-74° C. for 35-43 minutes at a stirring speed of 348-372 rpm. After the stirring is completed, the solution is filtered and dried to obtain oxidized coconut fiber. The coconut fiber has a diameter of 130-150 nm and a length of 0.2-0.4 mm; The mass concentration of the nitric acid solution is 60-64%; The mass ratio of the coconut fiber to the nitric acid solution is 9.5-10.6:70-82.

4. The method for preparing low shrinkage concrete according to claim 1, characterized in that: In the modification step, the mass volume ratio of the diphenylmethane diisocyanate, acetone, and primary coconut fiber is 2.2-2.4 g:310-330 mL:1.42-1.46 g; The ultrasonic treatment has an ultrasonic time of 12-15 min, an ultrasonic power of 92-97 W, and an ultrasonic frequency of 38-43 kHz.

5. The method for preparing low shrinkage concrete according to claim 1, characterized in that: In the step of preparing the modified basalt powder, the particle size of the basalt powder is 105-115 nm; The mass concentration of the ethanol solution is 37-42%; The mass ratio of the basalt powder, ethanol solution, sodium α-olefin sulfonate, octadecyl dimethyl betaine and treatment liquid is 8.2-8.6:64-70:0.2-0.4:0.4-0.6:12.0-12.5; In the treatment liquid, the mass ratio of 35wt% ethanol solution, diethylenetriaminepropyltrimethoxysilane and triethanolamine is 10-12:0.7-0.9:0.3-0.5; The mass volume ratio of the ammoniated basalt powder, xylene and maleic anhydride is 5.0-5.4 g:220-235 mL:1.7-1.9 g.

6. The method for preparing low shrinkage concrete according to claim 1, characterized in that: In the compounding step, the mass volume ratio of the modified coconut fiber, acetone, modified basalt powder and dibutyltin dilaurate is 2.0-2.2g:195-205mL:4.8-5.2g:0.22-0.24g.

7. The method for preparing low shrinkage concrete according to claim 1, characterized in that: The slurry mixing step comprises mixing cement, mineral powder and fly ash, stirring evenly, then adding crushed stone, river sand and vermiculite, stirring evenly again, adding functional composite material, polycarboxylate water reducer, sodium lignin sulfonate, fatty alcohol polyoxyethylene ether and deionized water, and performing homogenization treatment, wherein the homogenization time is 2.5-3.5 minutes, the homogenization pressure is 2.8-3.1 MPa, the homogenization times are 3 times, and after the homogenization treatment is completed, low shrinkage concrete is obtained.

8. The method for preparing low shrinkage concrete according to claim 7, characterized in that: The cement is P·O42.5 silicate cement; The particle size of the fly ash is 38-42 μm; The particle size of the crushed stone is 6.4-6.6 mm; The particle size of the river sand is 1.3-1.7 mm; The vermiculite has a particle size of 5.4-5.6 mm and a density of 2.57-2.62 g / cm 3 , the mass content of silicon dioxide is 40.3-41.2%.

9. The method for preparing low shrinkage concrete according to claim 7, characterized in that: The mass ratio of the cement, mineral powder, fly ash, crushed stone, river sand, vermiculite, functional composite material, polycarboxylic acid water reducer, sodium lignin sulfonate, fatty alcohol polyoxyethylene ether and deionized water is 10.3-10.7:3.8-4.2:3.7-3.9:34-38:23-25:15-17:6.1-6.3:0.2-0.4:0.10-0.14:0.12-0.15:15.7-16.3.

Citation Information

Patent Citations

  • Anti-carbonization concrete tubular pile and preparation method therefor

    CN105036647A

  • High-strength corrosion-resistant concrete material and preparation method thereof

    CN111732379A